2016
DOI: 10.18632/oncotarget.11508
|View full text |Cite
|
Sign up to set email alerts
|

Fusion between cancer cells and macrophages occurs in a murine model of spontaneous neu+ breast cancer without increasing its metastatic potential

Abstract: Cell fusion between neoplastic and normal cells has been suggested to play a role in the acquisition of a malignant phenotype. Several studies have pointed to the macrophage as the normal partner in this fusion, suggesting that the fused cells could acquire new invasive properties and become able to disseminate to distant organs. However, this conclusion is mainly based on studies with transplantable cell lines. We tested the occurrence of cell fusion in the MMTV-neu model of mouse mammary carcinoma. In the fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 43 publications
0
23
0
Order By: Relevance
“…Cell fusion between immune and neoplastic cells initiating tumorigenesis and affecting progression is an untested, century-old hypothesis ( 9 , 10 ) that has been only circumstantially examined ( 10 , 12 , 17 , 31 , 33 37 ). Reports of cells located in tumors containing components of both immune and neoplastic cells are increasingly frequent ( 1 , 10 13 , 16 , 17 , 19 , 35 , 38 44 ), although without strong evidence of etiologic mechanism or physiologic relevance. Early in vitro studies revealed that cell fusion hybrids displayed reduced cell doubling times relative to their genetic burden ( 45 ).…”
Section: Discussionmentioning
confidence: 99%
“…Cell fusion between immune and neoplastic cells initiating tumorigenesis and affecting progression is an untested, century-old hypothesis ( 9 , 10 ) that has been only circumstantially examined ( 10 , 12 , 17 , 31 , 33 37 ). Reports of cells located in tumors containing components of both immune and neoplastic cells are increasingly frequent ( 1 , 10 13 , 16 , 17 , 19 , 35 , 38 44 ), although without strong evidence of etiologic mechanism or physiologic relevance. Early in vitro studies revealed that cell fusion hybrids displayed reduced cell doubling times relative to their genetic burden ( 45 ).…”
Section: Discussionmentioning
confidence: 99%
“…Although CD163 is primarily expressed on monocytes and macrophages it has been detected on tumor cells with high malignant potential. However, tumor cell lines do not express CD163, even after stimulation with macrophage activating cytokines, so it has been hypothesized that tumor cells fuse with macrophages becoming more genetically unstable and aggressive (110). Assessment of patient tissues with CD163-positive tumor cells correlated with higher tumor grade, invasiveness, radioresistance and poor progression free-and overall survival in melanoma (111), breast (54,112,113), CRC (113), renal cell (114), and gastric (115) carcinomas.…”
Section: Iron Uptakementioning
confidence: 99%
“…In fact, there have been a plethora of in vitro and in vivo studies in the past decades demonstrating that tumor cells do fuse with normal cells, such as macrophages, fibroblasts, stromal cells or stem cells, thereby giving rise to viable proliferating TN-hybrid cells with properties that are linked with tumor progression including enhanced tumorigenic and metastatic capacity or enhanced drug resistance [7,8,9,10,11,12,13,14,15,16,17,18,19,20,21,22,23,24,25,26,27,28,29,30,31]. Likewise, several studies have reported putative TN-hybrid cells in human cancers, in some cases comprising up to 40% of tumors [7,13,20,25,32,33,34,35,36,37,38,39,40,41,42].…”
Section: Introductionmentioning
confidence: 99%